Burns Across Seasons: Seasonal Effect on the Mechanism of Burn Injuries in Pediatric Patients Requiring Hospitalization - Rafiq, Hafiza Mariam; Bashir, Muhammad Kashif; Noor ul Haq, Mahwish; Khaliq Siddiqi, Umair; Aman, Nadir; Yousaf, Abdullah (Indus Journal of Bioscience Research, 2024)
Background: Burn injuries are a major cause of trauma in pediatric patients, comprising 17–25% of total burn admissions and ranking among the five most deadly childhood injuries. Seasonal variations significantly influence burn mechanisms due to changes in environmental conditions and activities. Scald injuries peak during colder months with increased use of hot water and heating appliances, while warmer months see more contact and electrical burns from outdoor activities and power surges. Despite the high burden in developing nations, limited research explores these seasonal patterns. Objectives: This study aimed to investigate the seasonal relationship with burn injury mechanisms in pediatric patients under 13 years of age. Specifically, it sought to identify seasonal variations in burn types, quantify hospitalizations across seasons, and assess associated hospital stay durations. Methods: A prospective analytical cross-sectional study was conducted at Mayo Hospital Lahore/KEMU from December 2023 to August 2024, including 120 pediatric patients with burns involving ≥10% of total body surface area (TBSA), face, hand, perineum, or signs of inhalation injury. Data were collected on scalds, flame burns, and electric burns, defined by standard classifications. Results: Among 120 patients, scalds (77 cases) were the most common, followed by flame burns (33 cases) and electric burns (9 cases). Scalds and flame burns peaked in winter (49% and 58%, respectively), while electric burns were most frequent in summer. Scalds and electric burns showed higher severity in summer, whereas flame burns exhibited consistent severity across seasons.